Model of Students' Prophetic Character Building of Madrasah Aliyah in Responding to Global Sociocultural Change Era - M Arief Affandi; Nur Ali; Ahmad Barizi (STAI Hubbulwathan Duri, 2024)
This study aims to uncover and formulate a conceptual model, implementation strategy, and impact assessment of building prophetic character in students to address sociocultural changes in the global era. Using a qualitative multi-case study design, research was conducted at Madrasah Aliyah Swasta (MAS) Al-Ittifaqiah 2 Ogan Ilir and Madrasah Aliyah Negeri (MAN) 3 Palembang. Data were collected through observations, interviews, and documentation. Findings reveal that the vision is based on four pillars—the Qur'an and Hadith, culture, Pancasila, and government—while addressing consumer needs and anticipating sociocultural changes. This vision incorporates values of humanization, liberation, and transcendence, aiming to create